Documents on the laws of war - Roberts, Adam.; Guelff, Richard, 1950- (Oxford : Oxford University Press, 1999)
This new edition has been revised and updated to take account of the many diplomatic, legal and military developments of the last ten years. Conflicts in the Persian Gulf, the Balkans and Rwanda have ensured that the laws of war remain relevant.
Previous edition: Oxford: Clarendon, 1989.
Keywords: War (International law)